2004
DOI: 10.1111/j.1750-3639.2004.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Expression Profiles of Cerebellar Liponeurocytomas

Abstract: Cerebellar liponeurocytoma, a rare, newly identified CNS neoplasm of adults, is characterized by advanced neuronal/neurocytic and focal lipomatous differentiation, low proliferative potential and a favorable clinical prognosis. Despite the different age distribution and benign biological behavior, the cerebellar liponeurocytoma shares several features with the cerebellar medulloblastoma, which may include an origin from the periventricular matrix of the fourth ventricle or the external granular layer of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 46 publications
0
71
0
Order By: Relevance
“…The MIB-1 (Ki-67) labeling index is typically between 1% and 3% but may be higher. 10,11 Ultrastructural studies have confirmed large, nonmembrane-bound lipid deposits within the cytoplasm of tumor cells. Such cells nevertheless retain features of neuronal differentiation, including dense core neurosecretory granules, microtubules, and synaptic junctions containing clear vesicles.…”
Section: Pathologic Findingsmentioning
confidence: 91%
See 2 more Smart Citations
“…The MIB-1 (Ki-67) labeling index is typically between 1% and 3% but may be higher. 10,11 Ultrastructural studies have confirmed large, nonmembrane-bound lipid deposits within the cytoplasm of tumor cells. Such cells nevertheless retain features of neuronal differentiation, including dense core neurosecretory granules, microtubules, and synaptic junctions containing clear vesicles.…”
Section: Pathologic Findingsmentioning
confidence: 91%
“…Due to the paucity of long-term follow-up data, it is unclear whether radiation should be given in the immediate postoperative period or be reserved for recurrent tumor, which may occur many years following initial surgery. 10,11 When administered, radiotherapy is generally limited to the posterior fossa. 5 No cases of spinal …”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that central neurocytomas are genetically distinct from oligodendrogliomas. Although the expression profiles of cerebellar liponeurocytomas appear to have a closer relationship to those of central neurocytomas, the lack of TP53 mutations in central neurocytomas suggests the involvement of different genetic pathways (60,66,67).…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…In the 29 patients with cerebellar liponeurocytoma reported ( 182,185,186,187,188,189), the mean age was around 50 years (range, 24-77 years), with a peak in the third to sixth decade of life. This is in contrast with the age distribution of cerebellar medulloblastomas, more than 70% of which occur in children (178).…”
Section: Age and Sex Distributionmentioning
confidence: 99%